Taxonomic diversity of the intestinal microbiome landscape and its clinical significance in recurrent pregnancy loss - A. V. Tormozova; A. A. Erakaeva; G. A. Ibadullaeva; A. S. Galata; A. S. Asinovskaya; D. E. Kuzyura; K. N. Efremova; V. M. Chos; U. V. Svarnik; A. A. Dyachenko; A. N. Mavlyutova; L. A. Mukosiy; et al. (Акушерство, гинекология и репродукция)
Aim: to study taxonomic diversity of the intestinal microbiome landscape in relation to neuro-immune-humoral biomarkers in patients with recurrent pregnancy loss (RPL).Materials and Methods. A cross-sectional comparative study was conducted by enrolling 55 pregnant women with history of RPL (main group) and 60 women with physiological pregnancy (control group). All women underwent serum tumor necrosis factor-alpha (TNF-α), interleukin (IL) IL-17, cortisol and melatonin levels assessment using enzyme-linked immunosorbent assay. The taxonomic composition of the intestinal microbiota at the birth level was examined using 16S ribosomal RNA gene sequencing. The Chao1, Sobs, and ACE (Abundance Coverage Estimator) indices were used to assess α-diversity of microbial community.Results. It was found that α-diversity of the bacterial community in patients with RPL was significantly decreased assessed by Chao1 index (p = 0.014). A significant decline in prevalence of the genera Bifidobacterium (p < 0.001), Lаchnоsріra (p = 0.032), Roseburia (p = 0.003), Соррососcus (p = 0.012) was established along with rise in Ruminососсus (p < 0.001) and Кlebsiеllа (p = 0.002) in women with RPL. Moreover, there were observed several significant relations: а positive correlation between abundance of Ruminococcus bacteria and TNF-α level (r = 0.49; p = 0.003), a negative correlation between abundance of Bifidobacterium and IL-17 (r = –0.54; p = 0.001), abundance of Lachnospira and cortisol level (r = –0.46; p = 0.002), as well as abundance of Coprococcus and melatonin level in blood serum (r = –0.58; p = 0.028).Conclusion. It was found out that patients with RPL are characterized by dysbiotic changes in the microbiome landscape. The statistically significant correlations between some microbiota representatives and neuro-immune-humoral biomarkers suggest that dysbiotic alterations in the intestine may be involved in developing immune disorders and dysregulation of the pineal-pituitary-adrenal axis underlying RPL pathogenesis.